2018
DOI: 10.1159/000494387
|View full text |Cite
|
Sign up to set email alerts
|

Expression Density of Receptors as a Potent Regulator of Cell Function and Property in Health and Pathology

Abstract: The expression of cytokine receptors has a crucial role in many cellular processes. Recent studies reported that changes of receptor expression could control the action of mediators on target cells. The initiation of different signaling pathways and, therefore, specific effects on cells, depends on certain components forming the cytokine-receptor complex. These mechanisms control the immune response and affect both the course of diseases (oncological, autoimmune, inflammatory) and the effectiveness of therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…It is noteworthy that the pathological processes occurring in the body can alter the expression levels of different receptor types, which may be one of the mechanisms explaining why immunocompetent cells exhibit different responses. This was supported by a number of publications showing that the major immune cell subsets differ in their expression and co-expression levels in healthy subjects and in patients with immune-mediated diseases being also associated with inflammation severity [2,8,9].…”
Section: Introductionmentioning
confidence: 68%
“…It is noteworthy that the pathological processes occurring in the body can alter the expression levels of different receptor types, which may be one of the mechanisms explaining why immunocompetent cells exhibit different responses. This was supported by a number of publications showing that the major immune cell subsets differ in their expression and co-expression levels in healthy subjects and in patients with immune-mediated diseases being also associated with inflammation severity [2,8,9].…”
Section: Introductionmentioning
confidence: 68%
“…An interesting variant of receptor redistribution was demonstrated for naive cytotoxic T cells compared with the healthy donors: the proportion of cells with type 1 receptors was dramatically increased, while the percentage of cells expressing type 2 receptors was sharply reduced. Since type 1 and type 2 receptors implement different functions, these changes may indicate a change in the nature of the response of these cells to cytokines [11,12], and as a result, a change in their functional activity in RA. Evidence suggests that triggering a signal through type 1 and type 2 receptors simultaneously has significant therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, fundamental questions regarding the effect of the distribution of different receptor types within a cell subpopulation on cellular functional activity, the threshold level of cellular responses after the binding of TNF-α to TNFRs, and whether switching between different signaling pathways by varying receptor expression density, remain unanswered. Previous studies reported variations in expression density and co-expression of TNFRs between the healthy cell populations and those under pathological conditions [6]. Nevertheless, the effects of these changes and their potential are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%